A Scoping Review on the Role of Religion in the Experience of IPV and Faith-Based Responses in Community and Counseling Settings. Issue 2 (June 2023) - Istratii, Romina; Ali, Parveen
Research on religion and intimate partner violence does not appear to have integrated well the current evidence on religion/spirituality, marital functioning, and mental health and lacks a cross-sectoral perspective that bridges psychology, public health, international development, anthropology, and sociology. A better integration could reveal how religious experience could be leveraged resourcefully in developing faith-based interventions engaging religious leaders and when counseling victims/survivors and perpetrators in religious contexts. The current scoping review explored (a) the influence of religious experience on the rationalizations, behaviors and mental state of victims/survivors and perpetrators, and (b) the approaches and effectiveness of faith-based interventions to respond to domestic violence engaging religious leaders, communities, and psychologists. In pursuing these questions, we aimed to overcome the dominance of Western definitions of intimate partner violence and religion by combining evidence from sectors that are more international-looking and studies from low-and middle-income societies that historically received less attention. The review suggests the need to move toward more diversified and holistic understandings of religion and more context-specific approaches to designing faith-based interventions and counseling responses that are theologically grounded and trauma-informed and embedded in the sociological realities of the individuals and communities they seek to support.